From the Alliance of Economies to the Alliance of Civilizations: Turkey's Strategic Role and Importance - Murat Doral (Journal of Global Initiatives, 2010)
In "The Clash of Civilizations;' Huntington hypothesized that the principal conflicts of global politics will occur between groups of different civilizations, and concluded that the "clash of civilizations" will dominate global politics in the future. In addition, Huntington declared Turkey as one of the "torn countries" and tried to make connections between its Muslim identity and its delayed ED membership. The growing trade and investments volume tell us that regardless of our differences, people around the world understand the benefits of economic cooperation and would prefer this route to starting a war of civilizations.